Addressing a building information modeling ownership issue based on DEMATEL analysis - Chai, Changsaar; Chong, Heap-Yih; Lee, Chia Kuang; Kueh, Ling Lee; Fan, Laura Su-Ling (American Society of Civil Engineers (ASCE), 2025)
Building information modeling (BIM) is now a mandatory requirement for projects exceeding RM 10 million (approximately USD 2.12 million) in Malaysia, underscoring the nation’s commitment to advancing BIM adoption. This requires a review of contracts for BIM’s legal aspects. Standardizing BIM contracts, especially on model ownership, is key to prevent disputes and ensure smooth project execution. However, Malaysia lacks a specific BIM contract form, exposing a significant gap in the legal framework. This study aims to bridge this gap by proposing the integration of BIM considerations into existing Malaysian construction contracts and examining the implications of BIM ownership. The research began with an in-depth analysis of legal challenges surrounding BIM model ownership and its associated impacts on the construction industry. Expert interviews were subsequently conducted to validate and enhance the findings, with insights analyzed using the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method. The research culminated in the proposal of revised contractual conditions, adapted to the existing clauses in PWD Forms, PAM, and FIDIC, ensuring their suitability and practicality for BIM implementation. The study, though limited to industry views, offers valuable insights into BIM’s contractual issues in Malaysia. It reveals BIM model ownership dynamics with a new framework showing cause and effect and also gives practical advice to stakeholders, defining roles and responsibilities to strengthen BIM’s legal integration.